Glucomanano esterificado em rações de frangos de corte alimentados com milho contaminado por fumonisinas - OLIVEIRA, Eduardo Miranda de (2012)
An experiment with 420 broiler chicks, male Cobb 500, with average weight of 44.6 g ± 0.5 g, was conducted to evaluate corn contaminated with fumonisins in diets containing or not mycotoxin absorbent based on sterified glucomannan (GME) at 0 and 0.1% diet concentration. Chicks were allotted in a completely randomized design and factorial arrangement 3 x 2 + 1 (time of exposition to contaminated corn seven, 21 and 35 days), adsorbent addition (0 and 0.1% in the diet) and control diet (corn non-contaminated with fumonisins) totalizing seven treatments with five replicates of 12 birds each. The diets formulated were prestarter, starter and growth containing contaminated corn by fumonisins with GME. Diets were based on corn and soybean meal to attend nutritional requirements proposed by Brazilian Tables. Variables evaluated were: weight gain, feed intake, feed conversion and livability at seven, 14, 21, 28 and 35 days of age. Metabolizability coefficient of dry matter, ether extract and protein in three metabolic assays were carried out from four to seven days, 18 to 21 days and 36 to 39 days of age. We also evaluated relative weight and length digestive organs, villous height and crypt depth of small intestine at seven, 21 and 35 days of age. Statistical analysis were performed with R software and average compared by Tukey test (5%). Supplementation of 0.1% of mycotoxin absorbant based on GME containing corn contaminated with fumonisins showed no positive affects on performance, but was able to maintain the coefficient of ether extract metabolizability in broilers. For the relative weight and length digestive organs was found that the duration of exposure to corn contaminated with fumonisin caused a reduction in the length of the large intestine and the presence of the additive showed no reduction on effects of fumonisins. Other organs of the digestive system weren´t affected by treatments. There was no significant interaction (p>0.05) between fumonisin and GME for villous height, crypt depth and relation villous:crypt in the duodenum, jejunum and ileum to seven days of age. On day 21, birds fed contaminated corn with fumonisins with or without the GME had lower villous height of duodenum, jejunum and ileum, and lower crypt depth in the duodenum, ileum and lower relation villous:crypt in the ileum compared to the birds that fed non-contaminated corn with fumonisins (p<0.05). At 35 days it was found that the presence fumonisin affect the intestine and the addition of GME can collaborate to reduce inflammatory reaction and express benefic effect the intestine.